Kontribusi Dakwah Ustadz Hanan Attaki Terhadap Anak Muda Di Media Sosial Instagram - Achmad Mustafid; Nuraida Nuraida; Anang Walian (ScidacPlus, 2023)
The contribution of da'wah to young people on social media is currently very influential for their lives where young people today need religious guidance, and currently da'wah does not have to be carried out only in mosques and Taklim assemblies, but da'wah must keep up with the times such as using social media which in the current era is an all-digital era, therefore the author of this research examines Ustadz Hanan Attaki in the title Contribution of Da'wah to Young People on Instagram Social Media. The purpose of this research is to find out how the contribution of Ustadz Hanan Attaki's da'wah to young people on Instagram social media with the method he uses. This study used library research using a qualitative method approach. This study uses data collection methods with documentation and observation methods. The results of the study are that Ustadz Hanan Attaki's contribution to young people on Instagram social media is very influential for their lives, many of them are young people who want to learn religion from him, so Ustadz Hanan Attaki creates a community of young people who want to study religion, known as youth hijrah. (Shift Media), as well as the jungle house or message_trend, why are young people so interested in Ustadz Hanan Attaki, young people are very interested in Hanan Attaki, that is, with his style of language, appearance, and method of delivery, he is very gentle and refers to the da'wah method in the Al-Quran surah An Nahl verse 125 namely the Bil Hikmah method, Mauidzatil Hasanah, and Mujaddalah.